Nb K-edge x-ray absorption investigation of the pressure induced amorphization in A-site deficient double perovskite La1/3NbO3. (8th January 2016) - Marini, C; Noked, O; Kantor, I; Joseph, B; Mathon, O; Shuker, R; Kennedy, B J; Pascarelli, S; Sterer, E
Abstract: Nb K-edge x-ray absorption spectroscopy is utilized to investigate the changes in the local structure of the A-site deficient double perovskite La1/3 NbO3 which undergoes a pressure induced irreversible amorphization. EXAFS results show that with increasing pressure up to 7.5 GPa, the average Nb–O bond distance decreases in agreement with the expected compression and tilting of the NbO6 octahedra. On the contrary, above 7.5 GPa, the average Nb–O bond distance show a tendency to increase. Significant changes in the Nb K-edge XANES spectrum with evident low energy shift of the pre-peak and the absorption edge is found to happen in La1/3 NbO3 above 6.3 GPa. These changes evidence a gradual reduction of the Nb cations from Nb 5+ towards Nb 4+ above 6.3 GPa. Such a valence change accompanied by the elongation of the average Nb–O bond distances in the octahedra, introduces repulsion forces between non-bonding adjacent oxygen anions in the unoccupied A-sites. Above a critical pressure, the Nb reduction mechanism can no longer be sustained by the changing local structure and amorphization occurs, apparently due to the build-up of local strain. EXAFS and XANES results indicate two distinct pressure regimes having different local and electronic response in the La1/3 NbO3 system before the occurence of the pressure induced amorphization at ∼14.5 GPa.